2021
DOI: 10.1101/2021.12.24.21268378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preserved Omicron Spike specific antibody binding and Fc-recognition across COVID-19 vaccine platforms

Abstract: Despite the dramatic spread of Omicron globally, even among highly vaccinated populations, death rates have not increased concomitantly. These data argue that alternative immune mechanisms, beyond neutralization, may continue to confer protection against severe disease. Beyond their ability to bind and block infection, antibodies contribute to control and clearance of multiple infections via their ability to direct antiviral immunity via Fc-effector mechanisms. Thus, here we probed the ability of vaccine induc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In terms of responses to VOC, the reductions in anti-S IgG to the Alpha and Delta variants observed in the older adults were similar to other reports in the general population [40]. For the Omicron variant, while reductions in live-virus neutralization in vaccinated serum from the general adult population have been reported, there were no reductions in anti-Omicron S IgG [41,42]. Given the importance of neutralizing and nonneutralizing functions of IgG in conferring protection against SARS-CoV-2 [43,44], the markedly lower anti-Omicron S IgG level in older adults, that persisted after receipt of a third vaccine dose, suggests that this population may be more vulnerable to disease caused by the Omicron variant than younger adults, and that reformulation of vaccines to target the Omicron variant would be beneficial.…”
Section: Discussionsupporting
confidence: 86%
“…In terms of responses to VOC, the reductions in anti-S IgG to the Alpha and Delta variants observed in the older adults were similar to other reports in the general population [40]. For the Omicron variant, while reductions in live-virus neutralization in vaccinated serum from the general adult population have been reported, there were no reductions in anti-Omicron S IgG [41,42]. Given the importance of neutralizing and nonneutralizing functions of IgG in conferring protection against SARS-CoV-2 [43,44], the markedly lower anti-Omicron S IgG level in older adults, that persisted after receipt of a third vaccine dose, suggests that this population may be more vulnerable to disease caused by the Omicron variant than younger adults, and that reformulation of vaccines to target the Omicron variant would be beneficial.…”
Section: Discussionsupporting
confidence: 86%
“…Although it has been suggested that Omicron is evasive to neutralizing antibodies induced by natural infection from previous variants or vaccine-elicited [ 11 ], we show that HCW who were not infected by Omicron during the five week period of this analysis had higher concentration of anti-spike IgG prior the symptomatic visit, with >1549 BAU/mL being the threshold suggestive of significant reduction in the risk of symptomatic Omicron infection. This might be due to some residual neutralization activity, or that anti-spike IgG recognizes the virus beyond neutralization via Fc-effector mechanisms, as recently suggested [ 12 ]. Protection can be achieved by prior infection (irrespective of the vaccination status) or by recent vaccination, with participants who were unvaccinated or those who received a single dose of Ad26.COV.2, most of whom more than eight months prior, showing significantly lower levels of anti-spike IgG.…”
Section: Discussionmentioning
confidence: 96%
“…The three vaccines viz. BNT162b2 and mRNA-1273 mRNA vaccines, and CoronaVac presented a persisting higher opsonophagocytic FcγR2a and cytotoxic FcγR3a receptor binding activity that continued to recognize, bind, and clear the virus even in the absence of antibody mediated neutralizing activity ( Bartsch et al, 2021 ).…”
Section: What If Neutralizing Antibodies Are Partially Effective Against Omicronmentioning
confidence: 99%